Risk sharing and monetary policy transmission - Sebastian Hauptmeier; Fédéric Holm-Hadulla; Théodore Renault (European Central Bank (ECB), 2022)
Using regionally disaggregated data on economic activity, we show that risk sharing plays a key role in shaping the real effects of monetary policy. With weak risk sharing, monetary policy shocks trigger a strong and durable response in output. With strong risk sharing, the response is attenuated, and output reverts to its initial level over the medium term. The attenuating impact of risk sharing via credit and factor markets concentrates over a two-year horizon, whereas fiscal risk sharing operates over longer horizons. Fiscal risk sharing especially benefits poorer regions by shielding them against persistent output contractions after tightening shocks.
Keywords: C32; E32; E52; 330; Monetary Policy; Risk Sharing; Regional Heterogeneity; Local Projections; Quantile Regressions